Optimal Unemployment Benefits in the Pandemic - Kurt Mitman; Stanislav Rabinovich (Institute of Labor Economics (IZA), 2020)
How should unemployment benefits vary in response to the economic crisis induced by the COVID-19 pandemic? We answer this question by computing the optimal unemployment insurance response to the COVID-induced recession.We compare the optimal policy to the provisions under the CARES Act—which substantially expanded unemployment insurance and sparked an ongoing debate over further increases—and several alternative scenarios. We find that it is optimal first to raise unemployment benefits but then to begin lowering them as the economy starts to reopen — despite unemployment remaining high. We also find that the 600 UI supplement payment implemented under CARES was close to the optimal policy. Extending this UI supplement for another six months would hamper the recovery and reduce welfare. On the other hand, a UI extension combined with a re-employment bonus would further increase welfare compared to CARES alone, with only minimal effects on unemployment.
Keywords: J65; E6; H1; 330; COVID-19; epidemic; unemployment insurance; optimal policy